Upper body strength and power are associated with shot speed in men's ice hockey - Bežák, J.; Pridal, V. (Acta Gymnica, 2017)
Background: Recent studies that addressed shot speed in ice hockey have focused on the relationship between shot speed and variables such as a player's skills or hockey stick construction and its properties. There has been a lack of evidence that considers the relationship between shot speed and player strength, particularly in players at the same skill level.